1987
DOI: 10.1073/pnas.84.9.2829
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary thrombophilia: identification of nonsense and missense mutations in the protein C gene.

Abstract: The structure of the gene for protein C, an anticoagulant serine protease, was analyzed in 29 unrelated patients with hereditary thrombophilia and protein C deficiency. Gene deletion(s) or gross rearrangement(s) was not demonstrable by Southern blot hybridization to cDNA probes. However, two unrelated patients showed a variant restriction pattern after Pvu U or BamHI digestion, due to mutations in the last exon: analysis of their pedigrees, including three or seven heterozygotes, respectively, with -50% reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…The variant c.del1212G, p.Gly404Glyfs17X was not previously described, while a frameshift in Trp342 leading to the same stop position as p.Gly343Alafs35X was previously reported [Reitsma et al, 1995]. Leu97X was not previously reported, while Cys120X was reported in a compound heterozygote (together with p. Asn371Thr) [Simioni et al, 1996] and Arg348X was associated (several times) mainly with type I deficiency [Romeo et al, 1987;Reitsma et al, 1995]. Finally, Glu71X was detected by us in a young girl who also carried two missense mutations, p.His108Asn and p.Ile213Thr (Table 2).…”
Section: Premature Stop Codonsmentioning
confidence: 92%
“…The variant c.del1212G, p.Gly404Glyfs17X was not previously described, while a frameshift in Trp342 leading to the same stop position as p.Gly343Alafs35X was previously reported [Reitsma et al, 1995]. Leu97X was not previously reported, while Cys120X was reported in a compound heterozygote (together with p. Asn371Thr) [Simioni et al, 1996] and Arg348X was associated (several times) mainly with type I deficiency [Romeo et al, 1987;Reitsma et al, 1995]. Finally, Glu71X was detected by us in a young girl who also carried two missense mutations, p.His108Asn and p.Ile213Thr (Table 2).…”
Section: Premature Stop Codonsmentioning
confidence: 92%
“…Point mutations resulting from C -. T transitions have been documented in the Xlinked deficiencies of factors VIII and IX (68,69) as well as in autosomal disorders (70)(71)(72)(73)(74). Therefore, Msp I and Taq I were chosen for the initial screening of genomic DNA from the Fabry families.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that heterozygous changes in these genes possibly have no early developmental consequences. Mutations in two of the affected genes-BANK1 and PROC-are associated with systemic lupus erythematosus (Kozyrev et al 2008) and thrombophilia (Romeo et al 1987), respectively. However, PROC and BANK1 duplications-as observed in our study-have not been reported to be associated with a clinical phenotype and the offspring carrying these de novo SVs appeared healthy at the time of sampling (aged 39 and 32).…”
Section: Functional Impact Of De Novo Structural Changesmentioning
confidence: 99%